An evaluation of financing without collateral to small and medium enterprises in Malaysia: a conceptual framework / Ikmal Khairulluzin Jamil, Roza Hazli Zakaria and Azmah Othman - Jamil, Ikmal Khairulluzin; Zakaria, Roza Hazli; Othman, Azmah (Universiti Teknologi MARA, Cawangan Melaka, 2019)
The challenges faced by SME to get access to formal lending are well-known. Lending to SME continue, but mostly it was backed up by collateral. However, providing collateral to secure financing is a mammoth task for SME. Establishment of credit guarantee company to woo commercial lenders to lend to SME is a strong signal that collateral remains strong in dictating the credit flow to the SME. Past studies have been too concentrating on collateral lending until the area of financing without collateral to SME has been neglected. Hence, it is vital to scrutiny the factor’s considered by the commercial lenders to grant credit to SME without collateral, as collateral is the main reason SMEs are being denied on the formal lending. Therefore, this conceptual paper was formed to discuss the factors that might influence lending to SME without collateral by examining diverse literature and past studies related to financing to SME.